PENGARUH PENGUNGKAPAN TANGGUNG JAWAB SOSIAL, RASIO INTENSITAS MODAL DAN RASIO INTENSITAS PERSEDIAAN TERHADAP PENGHINDARAN PAJAK - Yolanda Sianturi; Melinda Malau; Ganda Hutapea (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2021)
This study aims to determine the effect of corporate social responsibility disclosure, capital intensity ratio, inventory intensity ratio and tax avoidance. This study uses a sample of manufacturing companies listed on the Indonesia Stock Exchange during the 2016-2018 period. A total of 99 property and real estate company-year were sampled in this study. The sample technique used in this research is side purposive method. The data used in this research is secondary data. The research data was obtained from the website www.idx.co.id. The data obtained and collected were then processed using the SPSS version 24 application. The results showed that the effect of corporate social responsibility disclosure with a significance value, the ratio of capital intensity with a significance value, and the ratio of inventory intensity with a significance effect on tax avoidance. This study provides theoretical implications, namely disclosure of corporate social responsibility, capital intensity ratios, and inventory intensity ratios which have a positive effect on tax avoidance. The results of this study support the agency theory that high quality company profits will accurately reflect the company's operational performance and reduce corporate tax avoidance efforts.